Corrosion failure analysis of low alloy steel and carbon steel rebar in tropical marine atmospheric environment: Outdoor exposure and indoor test. (November 2021) - Dong, Baojun; Liu, Wei; Zhang, Tianyi; Chen, Longjun; Fan, Yueming; Zhao, Yonggang; Yang, Weijian; Banthukul, Wongpat
Highlights: Newly designed low-cost steel bar is well used in tropical marine atmospheric environment. Corrosion product films of newly designed low alloy steel bar and carbon steel bar is studied by outdoor exposure and immersion test. Fixture for simulating concrete steel rebar is designed. Improvement mechanism of Cr and Mo on the compactness of corrosion product films of steel rebar is proposed. Abstract: Carbon steel rebar seriously corrodes in severe tropical marine atmospheric environment, threatening the safety of building structures. Hence, it is of great significance to design and manufacture low-alloy steel rebar which can be used in tropical marine atmospheric environment. In the paper, both of the self-designed low alloy (LA-1) steel rebar and carbon steel (HRB400E) rebar has been exposed in Sriracha for two years. The corrosion rate of LA-1 steel rebar is only half of that of carbon steel rebar after two years. However, it is difficult to study the root cause of low alloy steel rebars' enhanced corrosion resistance by alloy elements due to the presence of a large amount of CaCO3 in the rust layer. Therefore, the mechanism of improving the protective effect of alloy elements on rust layer is further studied by dry/wet cycling corrosion tests to simulate a tropical marine atmosphere environment. The formation of dense product film on LA-1 steel surface is mainly because of the addition of Cr and Mo elements, leading to the corrosion rate of LA-1 steel rebar far less than that of HRB400E steel rebar. The protective film formed by molybdate in alkaline environment hinders the further corrosion of steel rebars. Cr(OH)3 formed by hydrolysis of Cr in low alloy steel rebars inhibits the growth of FeOOH in rust, resulting in the generation of smaller size of FeOOH particles. The experiment proves that the newly designed LA-1 steel rebar can be well applied in tropical marine atmospheric environment.